Competição num mercado globalizado x fidelidade aos princípios cooperativistas: o caso SICREDI/RS - Kotz, Evandro Jacó (Universidade do Vale do Rio do Sinos, 2007)
The credit cooperative has demonstrated an expressive growth in last decade in the State of Rio Grande do Sul, and, in this matter, the Sistema de Crédito Cooperativo – SICREDI RS has contributed for this development considerably. SICREDI RS, which is constituted by 55 cooperatives and 447 branches, is present in more than 400 cities and has more than 700.000 members. Since 1995, SICREDI RS strong growth has interested people in studying the main causes that have contributed for its development. In this context, this paper has the objective of verifying how the cooperative principles, specially the democracy and the inter-cooperation, are being respected and what is the influence of Banco Central do Brasil (Brazilian Central Bank) in the professionalism of cooperatives management. It is an exploratory descriptive research, elaborated through a case study. For that, it was analyzed documents and reports of SICREDI RS since its constitution e, after, the members, the managers, the board of directors and the sta
Competition at a global market X loyalty to the cooperative principles: sicredi rs case.
Keywords: crédito; SICREDI; cooperativa; cooperative; credit cooperative; democracy; inter-cooperation; self-management; system; Ciências Humanas